The problem to standardize the modern Ukrainian phytomeliorative terminology (word-formation aspect) - Петрова, Тетяна Олексіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
In the article the meaning of the notions “language norm”, “terminological norm”, “normative term”, “word-formation norm” has been specified. Besides the essence of the process to standardize terminology (or terminological standardization) has been ascertained. The Ukrainian phytomeliorative terms have been studied concerning a word- formation norm. The terms were codified in the branch dictionaries and fixed in the educational text-books and various manuals-paper and electronic ones. A considerable number of term units formed with deviation from the word-formation norm has been revealed. They are process and relative adjectives with the modelled after foreign pufferns suffixes and compound adjectives with the modelled after foreign pufferns elements – “-видный”, “-подобный”, first of all in the function sphere, less – in the fixation sphere. The approaches and rules to standardize terms formed with violations have been elaborated. The normative forms have been recommended.